2017
DOI: 10.1016/j.jbankfin.2017.03.019
|View full text |Cite
|
Sign up to set email alerts
|

The interbank network across the global financial crisis: Evidence from Italy

Abstract: This study examines the effects of the global financial crisis (GFC) on interbank market connectivity by using network analysis. More specifically, using data on Italian banks' bilateral interbank positions between 1998 and 2013, we analyze the impact of the following events on each bank's network centrality: the liquidity crisis in August 2007, the collapse of Lehman Brothers in September 2008, the Eurosystem's long-term refinancing operations (LTROs) between 2009 and 2012, the sovereign debt crisis in July 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 59 publications
3
18
0
Order By: Relevance
“…While most existing financial network analysis literatures focus on the stock markets or specific economy sectors [46][47][48], a variety of financial systems have been studied as financial network such as global financial institutions [39,40], world trade web [49,50], interbank markets [51][52][53][54], exchanges [55], monetary market [56], corporate networks [57,58], global banking [59], CDS market [60], and credit market [61].…”
Section: Literature Review Of Financial Network Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…While most existing financial network analysis literatures focus on the stock markets or specific economy sectors [46][47][48], a variety of financial systems have been studied as financial network such as global financial institutions [39,40], world trade web [49,50], interbank markets [51][52][53][54], exchanges [55], monetary market [56], corporate networks [57,58], global banking [59], CDS market [60], and credit market [61].…”
Section: Literature Review Of Financial Network Analysismentioning
confidence: 99%
“…Many major individual financial markets around the world have also been studied in network approach, such as US [62,63], China [64][65][66], Germany [67,68], EU [69][70][71], Brazil [33,72], Italian [53,56], Korea [73], Russia [74], and Mexico [36,75]. Furthermore, there is literature focusing on the cross-board global markets [76,77].…”
Section: Complexitymentioning
confidence: 99%
“…In other cases, as in the seminal paper [14], even if the theoretical framework applies to single firms, the empirical part focuses on the aggregate, sector network, due to lack of more granular data. The use of payments as a proxy of interactions between economic entities is not new and has been investigated mainly for banks [15][16][17][18][19] in the context of systemic risk studies, where, however, other choices to characterise interactions are possible [20][21][22][23]. Apparently much less is known about the payment network between firms, mostly because of lack of data.…”
mentioning
confidence: 99%
“…When discussing the real estate financial risk transmission in China, some scholars found that the financial risk of real estate will impact the land finance [62]. Related empirical evidence can also be found in, e.g., Martinez-Jaramillo et al [63], Paltalidis et al [64], and Affinito and Pozzolo [65].…”
Section: Zhang Hong and LImentioning
confidence: 88%